2019
DOI: 10.3390/jmse7090313
|View full text |Cite
|
Sign up to set email alerts
|

Load Transfer of Offshore Open-Ended Pipe Piles Considering the Effect of Soil Plugging

Abstract: Open-ended pipe piles have been increasingly used as the foundations for offshore structures. Considering the soil plugging effect, a novel analytical model is proposed in this paper to study the load transfer mechanism of open-ended pipe piles. A trilinear model for the external shaft friction was introduced, while a rigid plastic model was adopted to describe the load transfer at the pile-plug interface. Furthermore, an equilibrium equation of the soil plug was proposed, based on the hypothesis of a trilinea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…is method can be used in geotechnical engineering [25,[34][35][36], load transfer mechanism [31], soil failure [37,38], failure mechanism [39], micromechanisms [30], high-speed train operation [9], metro train operation [40,41], fluidization [27], particle migration [42], strain softening [43], and filling capacity of concrete [44].…”
Section: Discrete Element Methodmentioning
confidence: 99%
See 1 more Smart Citation
“…is method can be used in geotechnical engineering [25,[34][35][36], load transfer mechanism [31], soil failure [37,38], failure mechanism [39], micromechanisms [30], high-speed train operation [9], metro train operation [40,41], fluidization [27], particle migration [42], strain softening [43], and filling capacity of concrete [44].…”
Section: Discrete Element Methodmentioning
confidence: 99%
“…Fu et al [30] presented discrete element modeling to reveal the micromechanisms and macrobehaviors of the installation responses of rigid open-ended piles with different diameters (22.5, 45, and 90 mm). Meanwhile, Liu et al [31] revealed the load transfer processes of the open-ended piles. Currently, there are few discussions on the adoption of the discrete element method and on the effect on the pile-soil dynamic properties during the pile-pulling process.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the continuous improvement of meso-testing methods, such as SEM (Scanning Electron Microscope), TEM (Transmission Electron Microscope), AFM (Atomic Force Microscope), and other testing methods [33][34][35][36], can be used to conduct mesoscopic research on granular materials. Numerous scholars [36][37][38][39][40][41][42][43][44][45] applied advanced experimental methods to study granular materials and explore the friction characteristics of granular materials. It has been reported in the literature that the frictional force at the interface of granular materials is generated by ploughing [17], and the actual contact stress between particles is 0.8-2 Gpa.…”
Section: Introductionmentioning
confidence: 99%
“…When the soil plug is closed, the open-ended pile behaves similarly to the closed-ended pile [4]. The presence of soil plugs influence the form of pile load transfer [5,6].…”
Section: Introductionmentioning
confidence: 99%